2016
DOI: 10.1007/s40519-016-0319-z
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder severity and functional impairment: moderating effects of illness duration in a clinical sample

Abstract: Overall, this study established a link between ED severity, psychological distress and functional impairment indicating that both eating disorder severity and psychological distress are more strongly related to impaired role functioning for patients with more recent onset of an eating disorder. More research in the complex relationship between ED severity and functional impairment is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…Their use of three subscales ('dieting', 'bulimia' and 'oral control') of a larger measure [11] (see also [12]) did not allow for assessment of the predictive effect of distinct behaviours, such as binge eating or Symptoms associated with impairment 4 self-induced vomiting. Similar findings were reported by Davidsen et al [10], who found a strong association between eating psychopathology and functional impairment across three domains (work/school, social life/leisure, and family life/home responsibilities) in 159 patients participating in a treatment study on group psychotherapy for EDs.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…Their use of three subscales ('dieting', 'bulimia' and 'oral control') of a larger measure [11] (see also [12]) did not allow for assessment of the predictive effect of distinct behaviours, such as binge eating or Symptoms associated with impairment 4 self-induced vomiting. Similar findings were reported by Davidsen et al [10], who found a strong association between eating psychopathology and functional impairment across three domains (work/school, social life/leisure, and family life/home responsibilities) in 159 patients participating in a treatment study on group psychotherapy for EDs.…”
Section: Introductionsupporting
confidence: 89%
“…four remained as significant predictors when others were held constant. The first of these was a measure of general psychological distress, highlighting, firstly, the importance of using a measure of distress in such studies [8,10] and, secondly, that ED concerns remain significant when this is controlled for [36]. An interesting question relates to whether a measure of psychological distress predicts variance over and above symptoms such as anxiety and depression and this might be a goal of further studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations